Interreligiösa gruppers samarbete med kommuner i Sverige - Nordin, Magdalena (Politik, 2014)
In Swedish contemporary society we nd ongoing processes of secularization and the idea of secularism be- ing challenged by a growing religious plurality in society. e overall purpose of this article is to highlight what happens when religion in a secularized and secular society enter into the public sphere as a result of inter-religious groups’ collaboration with local authorities. is is done through interviews and observations of three inter-religious groups meetings during 2010 and 2011. e collaboration between the inter-religious groups and the local authorities were initiated as a result of perceived problems of integration in the society and aims to include religious communities in society which may change the ongoing processes of seculariza- tion. One of the major problems with the collaborations was related to which religious community could be included by reasons of economic resources, access to personnel and premises and the acceptance and establishment in society.